Dioxins: validation of food frequency questionnaire and intake in a group of adolescents - Joanna Zając; Agata Skop-Lewandowska; Jadwiga Helbin; Artur Potocki (Annals of Agricultural and Environmental Medicine, 2017)
Introduction A lot of has been heard about dioxins and dioxins-like compounds. These molecules are typically connected in public awareness with affairs. The main source of dioxins for humans is food (90% of typical exposition); thus, assessment of dioxins intake and monitoring of levels of dioxins in food remain an important issue.